The April 2017 Mw6.5 Botswana Earthquake: An Intraplate Event Triggered by Deep Fluids. Issue 17 (2nd September 2018) - Gardonio, B.; Jolivet, R.; Calais, E.; Leclère, H.
Abstract: Large earthquakes in stable continental regions remain puzzling as; unlike at plate boundaries, they do not result from the local buildup of strain driven by plate tectonics. The 2017 Mw 6.5, Bostwana normal faulting earthquake occurred in a region devoid from recent tectonic activity and where present‐day deformation is negligible. The depth of the event (29 ± 4 km), in a felsic lower crust where ductile deformation is expected, likely requires a transient pulse of fluids from a deep source to activate brittle faulting. The mainshock was preceded by two foreshock swarm‐like sequences that may be further evidence for fluid movement in a critically loaded fault network. Contrary to plate boundary events, the Mw 6.5 Botswana earthquake did not require prior localized stress or strain accumulation. We propose that the crust in stable continental regions, even long after the last tectonic episode, constitutes a reservoir of elastic stress that can be released episodically, for instance, as a result of deep fluid migration. Plain Language Summary: Most earthquakes occur at plate boundaries where stress and strain concentrate due to the continuous motion imposed by plate tectonics. However, a significant number of large earthquakes also occur within continents, far from any deforming area. How they are triggered and what is the source of the released stress in such a context are key questions that remain unresolved. We use geodetic data to show that the April 2017 Botswana earthquake, the largest intraplate earthquake in the last 30 years, occurred at a depth of 30 km where rocks flow and should not break. We explore potential mechanisms to explain rock failure at such depth and propose that a local pulse of fluid was responsible for a transient embrittlement of the lower crust. This example shows that, even long after previous mountain building episodes, the crust in stable continental regions remains a reservoir of stress that can be tapped in by earthquakes triggered by local perturbations, including pulses of deep fluids. Key Points: Our InSAR‐based estimate of the source parameters indicates a deep event with two probable families of models We detect a precursory phase using template matching at teleseismic distances to the mainshock A transient pulse of fluids is required to trigger this event, maybe a common stress perturbation at the origin of intraplate events